Visualisasi Ayat Kursi pada Ornamen Kursi Mimbar (Studi Living Qur’an di Masjid Quwwatul Islam Yogyakarta) - Hilmi, Moh. Abdulloh; Muflih, M.; Diaulhaq, Faisal (Islamika : Jurnal Ilmu-Ilmu Keislaman, 2025)
This article discusses the visualization of the Ayat al-Kursi (Verse of the Throne) on the pulpit chair in the Quwwatul Islam Mosque in Yogyakarta. The ornamentation of Ayat al-Kursi in the form of a chair signifies that the Quran has entered the realm of aesthetic dimensions. The decorative carving of Ayat al-Kursi displayed by the author is a result of the reception of a fusion between Javanese and Kalimantanese artistry with the Quran. In this context, the author employs Alfred Schlutz's theory to elucidate two phenomena, namely the because motive and the in-order-to motive. The findings of this research are twofold. Firstly, the inclusion of Ayat al-Kursi as an ornament on the pulpit chair is because this verse possesses extraordinary meaning and content, explicating the magnificence of Allah over all of His creations. Secondly, it serves as a reminder to the preachers and congregants to always remember Allah SWT and His omnipotence, as well as to encourage the congregants to frequent the mosque for worship. Thus, the presence of the Ayat al-Kursi ornament on the chair not only signifies aesthetic values but also holds a profound history and encapsulates religious values found within the Quran.